Environmental literacy profile of Muhammadiyah junior high school students in Malang city: Intervention without having to consider factors! - Husamah, H.; Rahardjanto, Abdulkadir; Hadi, Samsun; Lestari, Nurdiyah; Permana, Tutut Indria (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
Students of Muhammadiyah Junior High Schools and Muhammadiyah Islamic Junior High Schools need to have environmental literacy to practice environmentally friendly attitudes, become nature conservationists, and fulfill the school's role in serving education and the environment. However, there has been no mapping of EL profiles in Muhammadiyah Junior High Schools and Muhammadiyah Islamic Junior High Schools in Malang City. This study aims to analyze the EL profile of Muhammadiyah Junior High Schools and Muhammadiyah Islamic Junior High Schools in Malang City. Using a cross-sectional survey approach, EL data from 412 students in grades VII, VII, and IX in six Muhammadiyah schools were collected and analyzed based on gender, class, and parental education. The results showed that there were no significant differences in EL between male and female students, as well as between classes, and parental education. This study concludes that interventions or policies to improve environmental literacy can be applied universally, regardless of gender, grade level, or parental education.